2022
DOI: 10.34172/jpd.2022.10156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relation between disease severity with platelet distribution width, platelet large cell ratio, mean platelet volume and red cell distribution width in severe and critically ill hospitalized patients with coronavirus disease 2019

Abstract: Introduction: Hematological parameters are raised for classification and determining of prognosis in coronavirus disease 2019 (COVID-19). Objectives: The aim of this study is to determine the relation between severity of the illness and serum level of red cell distribution width (RDW), mean platelet volume (MPV), platelet distribution width (PDW) and platelet large cell ratio (P-LCR) in patients with COVID-19 focusing on severe and critically ill patients. Patients and Methods: In this cross-sectional investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…About 64.4% of the individuals were significantly sick. They demonstrated that red cell distribution width could be useful to discriminate the significantly sick cases with COVID-19 from severe one (1). Regarding this study, we intended to explain some points.…”
mentioning
confidence: 99%
“…About 64.4% of the individuals were significantly sick. They demonstrated that red cell distribution width could be useful to discriminate the significantly sick cases with COVID-19 from severe one (1). Regarding this study, we intended to explain some points.…”
mentioning
confidence: 99%